(untitled) (Indian Journal of Animal Production and Management, 2014)
Ten swamp buffalo calves were selected irrespective of sex and divided into two groups comprising of 5 nos of animals in each group. The physiological parameters that are related to thermal stress viz. body temperature, pulse rate and respiration rate were recorded twice daily for a period of 6 months. During morning hours, the average body temperature of the experimental calves was found to be 100.4°F in pre-monsoon months as compared to 101.1°F in monsoon months. During evening hours, the average body temperature of the experimental calves was found to be 101.4°F in pre-monsoon months as compared to 102.2°F in monsoon months. The pulse rate ranged from 55 to 62 per minute in the pre-monsoon months in comparision with to 57 to 65 per minute in the monsoon months. The lowest mean respiration rate was recorded as 17.0 ± 0.31 and the highest mean respiration rate was found to be 18.8 ± 0.41 per minute in the pre-monsoon months. The recorded respiration rates for the monsoon months were almost similar to those which observed in the pre-monsoon months. The average Temperature-Humidity Index (THI) of different months in the place of study was found to be 74.72, 76.75, 77.00, 78.00, 78.25 and 78.55 for the months of March, April, May, June, July and August, respectively. The present experiment revealed that there was a positive correlation between THI and physiological parameters. The body temperature showed strong correlation with THI in comparision to pulse rate as well as respiration rate.